Implementation of the Kurikulum Merdeka: A Case Study at Ogan Komering Ilir Regency Senior High School’s in Chemistry Classroom - Farwati, Ratna; Marfu’ah, Siti; Anisa, Anisa; Metafisika, Kartika (Proceeding International Conference on Religion, Science and Education, 2024)
This article analyzes the implementation of the Kurikulum Merdeka in the first year at senior high school of Ogan Komering Ilir Regency, with a focus on Chemistry subject. Kurikulum Merdeka is an educational initiative that aims to provide greater flexibility to schools in designing and implementing curricula according to local needs and student characteristics. This study uses acase study approach to understand how chemistry teachers adapt and apply the Kurikulum Merdeka in teaching Chemistry. Through in-depth interviews with Chemistry teachers and collection of classroom observation data, this article reveals the challenges and opportunities faced by schools in implementing the Kurikulum Merdeka. The findings show that adaptation of the curriculum by schools has resulted in variations in teaching methods, selection of learning materials, and assessment. Chemistry teachers feel the freedom to choose and arrange teaching materials that are more appropriate to the context of students, but at the same time are faced with the need to develop a consistent and structured study guide. The implementation of the Kurikulum Merdeka in the first year at senior high school of Ogan Komering Ilir Regency has brought significant changes in Chemistry learning. Although there are still some obstacles that need to be overcome, such as developing a more structured learning approach and adapting it to meet the needs of various students, the Kurikulum Merdeka provides an opportunity to explore the creative potential of teachers in designing learning experiences that are more relevant and interesting for students. Further research can be conducted to observe the further development of this implementation and its long-term impact on the learning of Chemistry in senior high school.